2006
DOI: 10.1681/asn.2005090993
|View full text |Cite
|
Sign up to set email alerts
|

Sirolimus Therapy after Early Cyclosporine Withdrawal Reduces the Risk for Cancer in Adult Renal Transplantation

Abstract: Sirolimus (SRL) is a mammalian target of rapamycin inhibitor that, in contrast to cyclosporine (CsA), has been shown to inhibit rather than promote cancers in experimental models. At 3 mo ؎ 2 wk after renal transplantation, 430 of 525 enrolled patients were randomly assigned to remain on SRL-CsA-steroids (ST) or to have CsA withdrawn and SRL troughs increased two-fold (SRL-ST). Median times to first skin and nonskin malignancies were compared between treatments using a survival analysis. Mean annualized rates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
217
1
11

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 437 publications
(235 citation statements)
references
References 23 publications
6
217
1
11
Order By: Relevance
“…Most prior studies, including randomized clinical trials, have centered around prevention and treatment of nonmelanoma skin cancers, as these are a common malignant complication following a kidney transplant (12)(13)(14). While some studies have indicated possible reductions in nonskin cancers with sirolimus use, few have been large enough to provide precise incidence rate comparisons (15,16,28,29).…”
Section: Discussionmentioning
confidence: 99%
“…Most prior studies, including randomized clinical trials, have centered around prevention and treatment of nonmelanoma skin cancers, as these are a common malignant complication following a kidney transplant (12)(13)(14). While some studies have indicated possible reductions in nonskin cancers with sirolimus use, few have been large enough to provide precise incidence rate comparisons (15,16,28,29).…”
Section: Discussionmentioning
confidence: 99%
“…62 In addition, sirolimus appears to be associated with a lower risk of developing and successful treatment of post-transplant malignancies including PTLD, skin carcinomas and Karposi's sarcoma. [63][64][65][66][67][68] These results suggest that sirolimus may minimize the risk of developing post-transplant malignancies while maintaining organ transplant viability and may be used to continue immunosuppression and inhibit malignancies recurrence in successfully treated patients.…”
Section: Clinical Activity Of Sirolimus and Derivativesmentioning
confidence: 91%
“…47,48 Several studies have reported successful regression of Kaposi's sarcoma and post-transplant lymphoproliferative disease while preserving renal function after replacement of CNI with mTORIs. 49,50 The CONVERT trial revealed a signifi cantly lower incidence of new cancers in patients converted to SRL compared with those continuing on CNI at 12 and 24 months.…”
Section: The Role Of Mtor Inhibitionmentioning
confidence: 99%
“…Due to potential toxicities, knowledge of the adverse effects and pharmacokinetic profi les of mTOR-Is is necessary for proper management of patients receiving these agents. malignancies seen in studies [11][12][13] and their potential role in cardiovascular risk reduction following transplantation.…”
mentioning
confidence: 99%